Semi-classical transport in MoS2 and MoS2 transistors by a Monte Carlo approach. (June 2022) - Pilotto, A.; Khakbaz, P.; Palestri, P.; Esseni, D.
Highlights: We have developed a multi-valley Monte Carlo simulator to analyze, in uniform transport conditions, the effects of different scattering mechanisms on the saturation velocity of monolayer MoS2. Scattering mechanisms such as neutral defects and Coulomb centers strongly affect the mobility, but their effect on the saturation velocity is only modest. Scattering with surface optical phonons has a significant influence on the saturation velocity. Abstract: We have developed a multi-valley Monte Carlo simulator to study uniform electric field as well as quasi-ballistic transport in two-dimensional semiconductors, here applied to the case of MoS2 . At low electric field, the Monte Carlo results are in excellent agreement with a numerical solution of the linearized Boltzmann Transport Equation. The solver allows us to explore high field transport and to analyze the influence of different scattering mechanisms on the electron saturation velocity. In MoS2, scattering mechanisms such as neutral defects and Coulomb centers strongly affect the mobility, but their effect on the saturation velocity is only modest. Scattering with surface optical phonons, instead, has a significant influence on the saturation velocity, which we discuss based on the energy and momentum distributions of carriers provided by the Monte Carlo solver. Self-consistent simulations of a FET with 100 nm gate length point out the relevance of different scattering mechanisms and the presence or not of velocity saturation in the transistor channel.